UNGAN SOSIAL SEBAGAI STANDAR PERLAKUAN KHUSUS ORANG TUA TERHADAP ANAK PENDERITA KANKER DI YAYASAN KASIH ANAK KANKER INDONESIA(YKAKI) KOTA PEKANBARU - Muhammad Sukri; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This research was conducted in Pekanbaru City with the aim of explaining how social support is a standard for special treatment of parents for children with cancer and also explaining how parents are constrained in providing social support. This study uses descriptive qualitative research methods. Data collection was carried out using indepth interview techniques, direct observation and documentation. The results of the analysis show that social support is divided into four, namely emotional support, informative support, reward support, and instrumental support. In caring for and caring for children who are suffering from cancer, parents provide social support in order to increase the quality of life of their children. In providing social support, parents must be more patient in dealing with their children, this is because children who are suffering from cancer become more spoiled by their parents. In this study, there were several obstacles faced by parents in providing social support such as lack of education and information on how to care for and care for children who were suffering from cancer and also economic constraints in meeting all the needs of children. Keywords: Social support, Cancer children, Parents.